2013
DOI: 10.1016/j.ijpsycho.2012.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine predictors of complicated grief treatment outcomes

Abstract: Could sympathetic hyperarousal limit treatment success in complicated grief? The present study investigated persons with complicated grief, a chronic condition with distinct symptoms including persistent intense yearning and longing for the person who died, avoidance of reminders that the person is gone, deep relentless sadness, self-blame, bitterness, or anger in connection with the death, and an inability to gain satisfaction or joy through engaging in meaningful activities or relationships with significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…The available studies on the effects of these interventions found the intervention to reduce cortisol levels 94,95 . Furthermore, epinephrine levels predicted psychopathology‐related treatment outcomes suggesting that pre‐treatment stress levels moderated the effectiveness of the intervention 95 . In line with this, catecholamines were correlated with helplessness and hopelessness in the course of bereavement, 87 and thus can serve as endocrine markers of subjective burden and treatment effects.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…The available studies on the effects of these interventions found the intervention to reduce cortisol levels 94,95 . Furthermore, epinephrine levels predicted psychopathology‐related treatment outcomes suggesting that pre‐treatment stress levels moderated the effectiveness of the intervention 95 . In line with this, catecholamines were correlated with helplessness and hopelessness in the course of bereavement, 87 and thus can serve as endocrine markers of subjective burden and treatment effects.…”
Section: Discussionmentioning
confidence: 78%
“…The post‐treatment ICG‐score was significantly predicted by pre‐treatment epinephrine levels. SAM activity and autonomous function in the participants showed impaired CG outcomes after therapy 95 …”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations